LOVE LANGUAGE: Effects of the Sign Language Workshop on Social Isolation among Students with Hearing Impairment - Rose Carmel Tabotabo; April Joy Delina; Kim Rotante; Shendy Rabago; Glenvi Amores; Verdemerl Bacay (Journal of English as A Foreign Language Teaching and Research, 2025)
Deaf students often face social isolation in public schools, where they are a small minority among predominantly hearing peers and educators. Research indicates this leads to feelings of loneliness, limited social skills, and diminished self-esteem, all of which can adversely impact their academic performance. Consequently, school administrators and teachers are legally encouraged to address this concern. Research also highlights the importance of student involvement, particularly that of student leaders, who can significantly influence their schoolmates. This study aimed to assess the ability level of the student leaders in promoting inclusivity and helping reduce isolation for deaf students. This research evaluated the effectiveness of a sign language workshop intervention among student leaders on minimizing the social isolation of hard-of-hearing students. A purposive sampling approach was used to select participants for the study, consisting of 12 student leaders from SPED High School. These participants attended the workshop and completed a pretest-posttest using the Likert Scale to assess intervention effectiveness. The gathered data were analyzed using Microsoft Excel to calculate averages and rank results. Initially, the student leaders exhibited an overall pretest mean score of 2.13, signaling a lack of confidence and skills in supporting hearing-impaired peers. Post-workshop, their capacities markedly improved, with scores rising to 4.51 for enhancing inclusivity and 4.17 for reducing social isolation. These outcomes indicate that the training successfully boosted the student leaders' confidence and understanding, equipping them with vital skills to better advocate for and support hearing-impaired peers. In conclusion, focused training programs or workshops are crucial for empowering student leaders to foster inclusivity and reduce social isolation.